On some Haploops species collected in the North Atlantic Ocean with the description of Haploops islandica n. sp. (Crustacea: Gammaridea: Ampeliscidae) [Contribution to the knowledge of the Haploops genus. 8.] - Kaim-Malka, R.a.; Bellan-Santini, D.; Dauvin, J-C. (Zootaxa, 2016)
Four Haploops species collected in the North Atlantic Ocean are studied. One of them, H. islandica is a new species for the science. The three other species, H. carinata, H. setosa, H. robusta, were described from a long time, but many confusions exist about these species because their morphological nearness. The four species are described and illustrated in detail, and their distribution around the Iceland is specified. A key of the 23 species known nowadays is given permetting to separate the different species of the Haploops genus.